Bears - Kuchalla, Susan; Kelleher, Kathie (Mahwah, N.J. : Troll Associates, 1982)
Brief text and pictures portray the characteristics and habits of bears.
2.3
K-3
Keywords: Bears -- Juvenile literature; Bears; Bears